Socioeconomic and cultural differences in lexical comprehension - Alam, Florencia (2024)
The majority of the studies that have documented the effects of social inequality on lexical comprehension were built on a relatively small range of SES variation, since caregiver’s education generally ranges between 12 and 16 years of schooling in the samples analyzed. Furthermore, almost all the studies have been carried out in the USA or in Western Europe. This paper delves into the impact of SES on the comprehension of different types of content words in Spanish-speaking Argentinian children, a population in which socio-economic differences are more striking than in the previously studied populations.